Importance of Identification of Blood Group Sub-Types A1, A2, A1B and A2B For Blood Transfusion Safety - Yadav, Amita; Gupta, Anita; Sharma, Rakesh (Annals of Pathology and Laboratory Medicine, 2019)
Background: Karl Landsteiner, discovered ABO blood group system. In 1911.Von Dungern described two different A antigens based on reaction between A antigen on RBC, anti-A and anti-A1. A1 and A2 are the major subtypes of blood group A and differ from each other both qualitatively and quantitatively. The cells of approximately 80% of all group A or AB individuals are A1 or A1B and 20% remaining are A2 or A2B or weaker subtypes. Polymorphisms in the genes may lead to diminished amounts of A or B antigens on red blood cells giving rise to subtypes. These subgroups can result in discrepancy in ABO blood typing which can lead to serious transfusion reactions. Our objective was to assess the importance of identification of these subtypes. Methods: This was a prospective study of blood groups of donors in blood bank of Indira Gandhi Mahila Evam Balya Chikitsalaya, Bhopal (MP), India. The data of the subtypes of A and AB was analysed. Result: Analysis of 720 blood donors was done. Out of 166 donors of A group, 151 (91.0%) belonged to A1 subtype and only 15 (9.0%) belonged to A2. Of 64 donors with group AB, 54 (84.37%) belonged to A1B subtype and 10 (15.63%) belonged to A2B. It was noted that A2 in AB blood-group, as A2B, was more frequent in occurrence than presence of A2 as an A blood group. Conclusion: By proper assessment of these subtypes and incorporating them in ABO typing, rare but dangerous transfusion reactions can be avoided.